2008
DOI: 10.1007/s00404-008-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal osseous metaplasia

Abstract: To our knowledge, this finding has not been reported yet in the English medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…9 It is an endogenous non neoplastic pathological disorder which may also involve the cervix, ovary and the vagina. 4,[10][11][12] Majority of the affected patients are in the reproductive age group, though a rare case of post-menopausal osseous metaplasia of endometrium has been reported by Shimizu et al 13 Almost all the patients have a history of previous first trimester abortions, spontaneous or induced. [2][3][4][5] The time interval between previous abortion and diagnosis of osseous metaplasia may vary from 8 weeks to 14 years, however, cases up to 37 years after abortion have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is an endogenous non neoplastic pathological disorder which may also involve the cervix, ovary and the vagina. 4,[10][11][12] Majority of the affected patients are in the reproductive age group, though a rare case of post-menopausal osseous metaplasia of endometrium has been reported by Shimizu et al 13 Almost all the patients have a history of previous first trimester abortions, spontaneous or induced. [2][3][4][5] The time interval between previous abortion and diagnosis of osseous metaplasia may vary from 8 weeks to 14 years, however, cases up to 37 years after abortion have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ossification has also been reported in the cervix, the ovary, and the vagina [2,10-12]. To the best of our knowledge, this is the first reported case of osseous metaplasia nodules of both the submucosa and mesosalpinx.…”
Section: Discussionmentioning
confidence: 76%
“…Three cases reported with menstrual irregularities alone [5,6]. Other sites of ossification are vagina [7], cervix [8] and ovary [9]. Previous case reports [1,10,11] have shown that antecedent abortion were present in most patients (76.5%).…”
Section: Discussionmentioning
confidence: 99%